2005
DOI: 10.1016/j.jcrs.2004.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of the lens haptic plane concept with transformed axial lengths

Abstract: The LHP concept in combination with thick-lens ray tracing achieved MAE comparable to that with currently used formulas. The lack of trend with axial length is important for patients with short and long eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…An error of 1.00 D in keratometry translates into a 1.00 D error in refractive error after IOL implantation. 21 Taking into account that the mean absolute refractive error after modern optimized phacoemulsification is approximately 0.40 to 0.50 D, [22][23][24] an improvement in the accuracy of the prediction of the posterior corneal power by approximately 0.169 D, as we found (PostP calc À PostP actual versus PostP Gullstrand À PostP actual ), is significant.…”
Section: Discussionmentioning
confidence: 70%
“…An error of 1.00 D in keratometry translates into a 1.00 D error in refractive error after IOL implantation. 21 Taking into account that the mean absolute refractive error after modern optimized phacoemulsification is approximately 0.40 to 0.50 D, [22][23][24] an improvement in the accuracy of the prediction of the posterior corneal power by approximately 0.169 D, as we found (PostP calc À PostP actual versus PostP Gullstrand À PostP actual ), is significant.…”
Section: Discussionmentioning
confidence: 70%
“…A previous study 22 found a mean increase of 0.04 D in corneal power with an SD of 0.25 D measured by keratometry (not published in the article). However, that study was conducted before the advent of foldable IOLs and small-incision surgery.…”
Section: Other Sources Of Errormentioning
confidence: 73%
“…Norrby et al 22 also developed a thick-lens formula and deliberately limited the ACD prediction to the 2 parameters required for the optical calculation (AL and corneal radius). Corneal radius is reproducibly obtained by keratometry, 4 but its conversion to corneal power (K value) varies due to use of different keratometric indices.…”
Section: Expressed As Effect Inmentioning
confidence: 99%
“…Transformation of measured ALs is an option to cope with large errors. 12,13 Therefore, in this study, we propose a method of optimizing AL in long eyes.…”
Section: Discussionmentioning
confidence: 99%